Genetic ablation of solute carrier family 7a3a leads to hepatic steatosis in zebrafish during fasting. Issue 6 (4th November 2014) - Gu, Qilin; Yang, Xiaojie; Lin, Li; Li, Shaoyang; Li, Qing; Zhong, Shan; Peng, Jinrong; Cui, Zongbin
<x xml:space="preserve">Abstract</x> Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disorder caused by abnormal lipid metabolisms, such as reduced hepatic fatty acid oxidation (FAO), but intracellular control of FAO under physio‐ and pathological conditions remains largely undefined. Here, we demonstrate that deprivation of Slc7a3a leads to hepatic steatosis in fasted zebrafish as a result of defects in arginine‐dependent nitric oxide (NO) synthesis. Fast‐induced hepatic steatosis in slc7a3a‐null mutants can be rescued by treatments with NO donor, cyclic guanosine monophosphate analog, adenosine‐monophosphate–activated protein kinase (AMPK) activator, or peroxisome proliferator‐activated receptor alpha (PPAR‐α) agonist. In contrast, inhibitors of NO synthases, AMPK, or soluble guanylate cyclase and liver‐specifically expressed dominant negatives of peroxisome proliferator‐activated receptor‐gamma coactivator 1 alpha and PPAR‐α are sufficient to induce hepatic steatosis in fasted wild‐type larvae. Moreover, knockdown of Slc7a3 in mice or SLC7A3 in human liver cells impaired AMPK‐PPAR‐α signaling and resulted in lipid accumulation under fasting or glucose starvation, respectively. Conclusion: These findings have revealed a NO‐AMPK‐PPAR‐α–signaling pathway that is crucial for the control of hepatic FAO in vertebrates. (Hepatology 2014;60:1928–1940)